Physiological, anatomical, and transcriptomic analyses reveal the effects of acid rain stress on Akebia trifoliata and the mitigation potential of exogenous curcumin - Xingmei TAO; Kai WANG; Xiaoxu BI; Yongfu ZHANG (Biologia Plantarum, 2025)
This study investigated the impacts of acid rain stress on Akebia trifoliata and the mitigation effects of exogenous curcumin (CUR) using integrated physiological, anatomical, and transcriptomic analyses. Acid rain stress significantly decreased chlorophyll content (total chlorophyll by 64.8%), leaf epidermal thickness (upper and lower epidermis by 58.9 and 35.6%), and starch content (by 63.9%), while increasing oxidative stress markers (MDA by 82.6%; ROS production by 345.8%) and content of osmolytes (proline by 64.4%). A. trifoliata counteracted acid rain stress by enhancing superoxide dismutase (SOD) and catalase (CAT) activities, and by modifying leaf anatomical structure (increased mesophyll tissue thickness). CUR application, particularly at 50 μmol/L (CUR50), effectively alleviated damage by maintaining leaf structural integrity and promoting growth recovery. Transcriptomic analysis revealed 993 differentially expressed genes between CUR50-treated vs. acid rain-stressed plants, primarily enriched in the plant hormone signal transduction and phenylpropanoid biosynthesis pathways. These results demonstrate that CUR mitigates acid rain stress through coordinated physiological adaptations and transcriptional reprogramming of stress-responsive pathways. This study provides a theoretical basis for cultivating A. trifoliata and implementing phytoremediation strategies in acid rain-affected regions.